The genetic aetiology of Silver–Russell syndrome. Issue 4 (21st December 2007) - Abu-Amero, S; Monk, D; Frost, J; Preece, M; Stanier, P; Moore, G E
Abstract : Silver–Russell syndrome (SRS MIM180860) is a disorder characterised by intrauterine and/or postnatal growth restriction and typical facies. However, the clinical picture is extremely diverse due to numerous diagnostic features reflecting a heterogeneous genetic disorder. The mode of inheritance is variable with sporadic cases also being described. Maternal uniparental disomy (mUPD) of chromosome 7 accounts for 10% of SRS cases and many candidate imprinted genes on 7 have been investigated. Chromosome 11 has moved to the forefront as the key chromosome in the aetiology, with reports of methylation defects in the H19 imprinted domain associated with the phenotype in 35–65% of SRS patients. Methylation aberrations have been described in a number of other imprinted growth related disorders such as Beckwith–Wiedmann syndrome. This review discusses these recent developments as well as the previous work on chromosome 7. Other candidate genes/chromosomal regions previously investigated are tabled.